Comparative Study of Lytic Activity and Specificity of Anthrax Bacteriophages Gamma A-26, K VIEV, VA-9 and Fah-VNIIVV&M Batches - T. M. Golovinskaya; N. P. Buravtseva; O. I. Tsygankova; E. I. Eremenko (Проблемы особо опасных инфекций, 2011)
Studied are diagnostic properties of four anthrax bacteriophages. Indicated are various spectra of specific lytic activity and specificity of bacteriophages Gamma A-26, K VIEV, VA-9 and Fah-VNIIVV&M. K VIEV, VA-9 bacteriophages with wide spectrum of specific activity possess relatively low specificity. On the contrary, Fah-VNIIVV&M bacteriophage with high specificity exhibited narrow spectrum of specific lytic activity. Gamma A-26 bacteriophage is proposed for application as a diagnostic one, as it lyzes B. anthracis strains of all types, its specificity being equal to 90 %.